Red deer (Cervus elaphus L.) - the first milestone in antler development - Dražen Degmečić; Tihomir Florijančić (Poljoprivreda, 2018)
Selection of males is based on two main parameters, degree of physical development (body weight) and the stage of secondary sexual characteristic development - antlers. Antlers can be characterized as a weapon which reflects the age, body weight and physiological condition. In particular, antler development is an indicator for selection of yearlings and young males too. Selection in age class „young males“ (age 3-5 years) is crucial for managing male side of red deer population. In this age class young males require a lot of energy because they experience, both skeletal and physical development. In this age class it is important to mention that important elements of antlers appear - tines and possible royal. The research was conducted in the Baranja Danube area from the fenced unit of the hunting area in the same nutritional and habitat conditions. Cast antlers of 13 males were measured during their life (individual approach). After the data processing special attention was given to the „young males“ age class. Trend of growth for all the observed parameters appeared. What occurred is the so-called first significant „jump - milestone“ of antler development. Significant development of antlers in young males appear in the fifth year of their life when the young males reach the required physical and skeletal development. Thus, development of antlers can’t jeopardize parallel operations of other body processes.